Can cholera 'hotspots' be converted to cholera 'coldspots' in cholera endemic countries? The Matlab, Bangladesh experience. (June 2020) - Zaman, K.; Ryun Kim, Deok; Ali, Mohammad; Ahmmed, Faisal; Im, Justin; Islam, Md Taufiqul; Khan, Ashraful Islam; Yunus, Md; Khan, Md Alfazal; Marks, Florian; Qadri, Firdausi; Kim, Jerome; et al.
Highlights: Matlab, Bangladesh was a well-documented cholera 'hotspot' – an area of regularly recurrent cholera with a high annual incidence – for many decades. In recent years, cholera has declined to negligible levels in Matlab, despite persistently high rates in many areas of Bangladesh and despite increasing local ambient and sea surface temperatures, which favor a high cholera incidence. The decline occurred following the provision of low-cost tubewells for the supply of water and inexpensive sanitary latrines to a high proportion of the population. These observations lend optimism to the success of the World Health Organization current global initiative to end preventable cholera by 2030. Abstract: Background: Cholera remains a major public health threat in low- and middle-income countries. The World Health Organization (WHO) has recently launched a global initiative to end preventable cholera by 2030. Key to the success of this initiative will be the elimination of cholera transmission in cholera 'hotspots' with regularly recurrent disease; this can be achieved via improved surveillance to define hotspot populations, through the use of oral cholera vaccines, and through the implementation of improved water, sanitation, and hygiene (WASH). Methods: This study was performed to analyze the trend in cholera incidence during the years 1974–2018 in Matlab, Bangladesh (defined population of about 200 000) that has been recognized as one of the world's cholera hotspots. During this period, Matlab has maintained a demographically defined population and comprehensive, culture-based surveillance for cholera, supplemented by periodic surveys to characterize the socioeconomic status of the population, as well as water sources and facilities for defecation. Results: Cholera transmission has nearly been eliminated in Matlab, despite a continuing high cholera burden in many other parts of Bangladesh and despite trends of increasing ambient and sea surface temperatures, which are known to increase cholera incidence. Concomitantly, the socioeconomic status of the population has increased modestly, and the use of simple tubewells for drinking water has reached 95% and the installation of sanitary latrines has reached 85%. Conclusions: The factors responsible for the decline in cholera are difficult to pinpoint precisely, but this decline has occurred with the installation of inexpensive improvements in water sources and latrines and despite environmental factors that should have augmented cholera incidence. These observations lend optimism to the current global initiative to end preventable cholera by 2030.